2007
DOI: 10.1007/s00421-007-0498-4
|View full text |Cite
|
Sign up to set email alerts
|

Maximal torque- and power-pedaling rate relationships for elite sprint cyclists in laboratory and field tests

Abstract: Performance models provide an opportunity to examine cycling in a broad parameter space. Variables used to drive such models have traditionally been measured in the laboratory. The assumption, however, that maximal laboratory power is similar to field power has received limited attention. The purpose of the study was to compare the maximal torque- and power-pedaling rate relationships during "all-out" sprints performed on laboratory ergometers and on moving bicycles with elite cyclists. Over a 3-day period, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
101
3
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(110 citation statements)
references
References 18 publications
(39 reference statements)
5
101
3
1
Order By: Relevance
“…The parabolic power-crank velocity relationship seen in this study emphasises the influence of crank rate on peak power. The optimum velocity for maximum power output was 125 rpm, which is surprisingly similar to the ω opt during elite track cycling (~ 129 rpm (Dorel et al 2005;Gardner et al 2007)). The relatively short upper limbs and greater crank length of grinding compared to cycling (250 vs 170 mm (Dorel et al 2005)) would be expected to lead to a greater joint excursion during each revolution with grinding.…”
Section: Minmentioning
confidence: 55%
See 1 more Smart Citation
“…The parabolic power-crank velocity relationship seen in this study emphasises the influence of crank rate on peak power. The optimum velocity for maximum power output was 125 rpm, which is surprisingly similar to the ω opt during elite track cycling (~ 129 rpm (Dorel et al 2005;Gardner et al 2007)). The relatively short upper limbs and greater crank length of grinding compared to cycling (250 vs 170 mm (Dorel et al 2005)) would be expected to lead to a greater joint excursion during each revolution with grinding.…”
Section: Minmentioning
confidence: 55%
“…This may have an important bearing on the selection of gear ratios and the optimisation of power production during big-boat sailing. During elite sprint cycling a polynomial power-velocity relationship has been described (Martin et al 1997;Dorel et al 2005;Gardner et al 2007), and contrary to the hyperbolic force-velocity relationship of isolated muscle (Wilkie 1949), the relationship between torque and velocity appears to be linear (Martin et al 1997;Dorel et al 2005;Gardner et al 2007;Sprague et al 2007). Similar results have been found during seated arm cranking (Vandewalle et al 1989;Vanderthommen et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Previous field-based BMX research has shown that peak power output (2087 ± 157W) occurred at a cadence of 212 ± 3.5revs·min -1 (Herman et al, 2009). Gardner et al (2007 ascertained that peak power (1791 ± 169W) occurred at much lower cadences (128 ± 7revs·min -1 ) in velodrome track sprint cyclists.…”
Section: Introductionmentioning
confidence: 91%
“…This graph was used to extrapolate an optimal theoretical cadence that elicited peak power (122 ± 18revs·min -1 ). Previous studies in this area (Sergeant et al, 1981;Vandewalle et al, 1985;Martin et al, 2007), albeit in other cycling disciplines, suggested that the parabolic shape used to identify optimal relationships cannot be used to accurately ascertain the relationship from a single test. Subsequently, the actual optimal cadence to elicit peak power in BMX cyclists may be different from that reported by Debraux and Bertucci (2011).…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, sports training professionals use different devices for training control in an increasingly widespread way (Gardner, Martin, Martin, Barras, & Jenkins, 2007;Halson, 2014;Mroczek, Kawczynski, Superlak, & Chmura, 2013), particularly the portable and easy-to-use ones. The development and improvement of practical and accessible evaluation methods to accurately measure performance are thus issues of high interest for creating individual workout plans.…”
Section: Introductionmentioning
confidence: 99%